2017
DOI: 10.1513/annalsats.201702-148sr
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance after Hospitalization and Critical Illness: A Systematic Review

Abstract: Sleep disturbance is common in critically ill patients up to 12 months after hospital discharge. Both subjective and objective studies, however, suggest that sleep disturbance improves over time. More research is needed to understand and optimize sleep in recovery from critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 69 publications
(172 reference statements)
7
119
2
3
Order By: Relevance
“…Few studies have rigorously evaluated the prevalence of sleep disruption after critical illness. A recent systematic review by Altman and colleagues reported on 22 studies examining sleep after hospital discharge in survivors of critical illness . Sleep disturbances were common, and despite improving over time, up to two‐thirds (61%) of patients still reported poor sleep at 6 months follow up .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have rigorously evaluated the prevalence of sleep disruption after critical illness. A recent systematic review by Altman and colleagues reported on 22 studies examining sleep after hospital discharge in survivors of critical illness . Sleep disturbances were common, and despite improving over time, up to two‐thirds (61%) of patients still reported poor sleep at 6 months follow up .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by Altman and colleagues reported on 22 studies examining sleep after hospital discharge in survivors of critical illness . Sleep disturbances were common, and despite improving over time, up to two‐thirds (61%) of patients still reported poor sleep at 6 months follow up . Analysis of risk factors for sleep disturbances was conflicting; however, persistent sleep disturbances were frequently associated with post‐discharge psychological comorbidities and impaired quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance seems to be a prominent problem for ICU survivors in other recent research (194). Altman et al's review from 2017 (194) found severe sleep disturbance at approx. 3 months to be in the range of 34-64%, and in the range of 10-61% after 6 months.…”
Section: Other Symptoms In Icu Survivorsmentioning
confidence: 95%
“…In addition, sleep disturbance is another common problem for ICU survivors including insomnia, nightmares, and poor-quality sleep [20]. Psychiatric symptoms, such as trauma-related symptoms and depressive symptoms, were associated with a higher likelihood of post-ICU sleep disturbances [21].…”
Section: Introductionmentioning
confidence: 99%